2003
DOI: 10.14214/sf.510
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced possibilities for analyzing tree structure as provided by an interface between different modelling systems

Abstract: In recent years, many different advanced mathematical models and simulation systems for tree and forest growth have been developed. We show a possibility to extend analysis tools for measured and simulated plants using a data interface between the simulation model LIGNUM and the multifunctional software system GROGRA. Both systems were developed by different teams. To demonstrate the enhanced possibilities for analyzing a LIGNUM tree, several examples are given. In these examples three different approaches for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Essentially the use of L is based on the similarity of how bracketed L systems and LIGNUM represent the branching structure of trees. Similar conversions between modelling frameworks and tools have been reported, for example, by Ferraro et al (2002) and Dzierzon et al (2003). In fact, already Kurth (1994b) reported convergence between tree models produced by AMAP and the same models expressed in L systems.…”
Section: Discussionsupporting
confidence: 79%
“…Essentially the use of L is based on the similarity of how bracketed L systems and LIGNUM represent the branching structure of trees. Similar conversions between modelling frameworks and tools have been reported, for example, by Ferraro et al (2002) and Dzierzon et al (2003). In fact, already Kurth (1994b) reported convergence between tree models produced by AMAP and the same models expressed in L systems.…”
Section: Discussionsupporting
confidence: 79%
“…trunks, branches, and small twigs) is larger during the defoliation stage resulting in a decrease of LAI. Current research on Norway spruce eco-physiological processes demonstrates possibility to describe mathematically distribution of the canopy foliage and woody structures (Dzierzon et al, 2003;Kuuluvainen & Sprugel, 1996). Consequently, such simplified structural relations can be incorporated into radiative transfer (RT) models, used for estimation of forest canopy bio-chemical and biophysical parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The ratio (p) was constant across branching orders with link diameters ≥1.5 cm (D min ). Previous studies have also reported that (1) although some descriptions of tree branch scaling have attempted to use a single uniform relationship governing proportions of trees and branches over their entire range of sizes, portions of plants below a certain critical size scaled differently (Bertram, 1989), (2) the average proportionality factor (p) may increase for smaller diameters (Camarero et al 2003;Richardson andzu Dohna 2003, Allen et al 2008) because smaller tree branches scale differently from larger branches (Betram 1989), and (3) several models have been parameterized by seemingly rigid morphogenetic rules, but shoot systems have exhibited a high degree of plasticity in their development (Bertram 1989;William 1997;Dzerzon et al 2003). The D o of Acacia, Gliricidia, and Leucaena, can be described by a constant p across branching orders with link diameter ≥1.5 cm.…”
Section: Functional Branching Properties Of the Shoot Systemsmentioning
confidence: 99%